2013
DOI: 10.3892/mmr.2013.1428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of OSW-1 on microRNA expression profiles of hepatoma cells and functions of novel microRNAs

Abstract: 3β,16β,17α-trihydroxycholest-5-en-22-one 16-O-(2-O-4-methoxybenzoyl-β-D-xylopyranosyl)-(1→3)- (2-O-acet​yl-α-L-arabinopyranoside) (OSW-1) is a member of the cholestane saponin family, which was first isolated from the bulbs of Ornithogalum saundersiae and previously reported to be cytotoxic against several types of malignant cells. However, its antitumor mechanism remains unclear. Therefore, we investigated microRNA (miRNA) expression profiles in order to explore the antitumor activities of OSW-1. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…OSW-1 is a natural compound that has shown considerable anticancer activity in several kinds of cancer cells, including pancreatic cancer, ovarian cancer, leukemia, human hepatomas, and malignant brain tumors (5,39). Herein we showed that OSW-1 can also inhibit colon cancer cells more powerfully than other drugs.…”
Section: Discussionmentioning
confidence: 74%
“…OSW-1 is a natural compound that has shown considerable anticancer activity in several kinds of cancer cells, including pancreatic cancer, ovarian cancer, leukemia, human hepatomas, and malignant brain tumors (5,39). Herein we showed that OSW-1 can also inhibit colon cancer cells more powerfully than other drugs.…”
Section: Discussionmentioning
confidence: 74%
“…All of the signaling pathways and biological processes that the putative target genes are involved in are concerned with adipocyte differentiation and metabolism, so we hypothesized that miR-1908 would have an effect on the differentiation and metabolism of human adipocytes. Additionally, miR-1908 has been identified as having a close relationship with the processes of metastatic invasion, angiogenesis, and colonization of melanomas [22]; it may be involved in the malignant progression of chordoma [33]; and may participate in the formation of hepatoma cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-299-5p was downregulated in patients with t (11q23)/MLL-rearrangement and upregulated in t (15:17) cytogenetic subtypes [35]. Another study on hepatoma cells showed that hsa-miR-299-5p targeted osteopontin (OPN), which is known to be essential for enhancing proliferation and tumorigenicity [36]. Gain- and loss-of-function experiments revealed that miR-299-5p plays a role in the regulation of hematopoietic progenitor; it may therefore act as miRNA in the differentiation of megakaryoblasts [37].…”
Section: Discussionmentioning
confidence: 99%